A different approach to solar cell simulation. (October 2015) - Kavasoglu, Nese; Kavasoglu, A. Sertap; Metin, Bengul
Graphical abstract: Highlights: A new simulation program has been developed and operated for the Au/ n -GaN device. Device inhomogeneity is introduced to program via fluctuation factor term. The barrier height fluctuation factor strongly affects the device characteristics. Abstract: Zero barrier height inhomogeneity in the device is generally assumed to conform to Gaussian distribution in the literature. In this study, zero barrier height inhomogeneity has been adopted to obey random distribution. Cell was divided into elementary diodes, which were connected in parallel to each other. The current–voltage characteristics of the cell were obtained by developed device modeling program for various zero barrier height inhomogeneity levels at room temperature in dark and under light conditions. The cell parameters were then calculated by using simulated current–voltage data. It is displayed that increase in zero barrier height inhomogeneity results in Schottky barrier height enhancement and decrease in the diode factor of the cell. Fill factor and V oc values showed a decreasing trend with increasing zero barrier height inhomogeneity. Also, random distribution of zero barrier height effect on interface state density was examined. Interface state density increases with increasing zero barrier height inhomogeneity.